EMISI DAN ABSORPSI GAS METANA PADA SISTEM PENANAMAN PADI DI AREA TANAH SAWAH - Salim, Marniati; Faizah, Hiyal; Sudiana, I Made (Universitas Andalas, 2010)
To know there are emission and methane absorption, research was conduted by measuring directly gas methane at the rice field and absorption with metanotroph bactery using chromatography gas. From the research, we know that there is methane gas emission at the rice field. Watery land condition, emit methane gas (2,309 mg/L) larger than not watery land (0,059 mg/L). At the same time and paddy age is 2 month, it also emit larger methane gas (1,809 mg/L) than 1 month age paddy (1,758 mg/L) and without paddy (0,697 mg/L), whereas for methane absorption at land sample T0, T1, T2, T3, shows that with fertilizer given can increase the reduction of injected methane gas. Keywords: Absorption, Metanotroph bacteria, Methane gas emission